2015
DOI: 10.1615/critreveukaryotgeneexpr.2015013358
|View full text |Cite
|
Sign up to set email alerts
|

Zingiber officinale and Type 2 Diabetes Mellitus: Evidence from Experimental Studies

Abstract: Zingiber officinale is being used as diet-based therapy because of its wide therapeutic potential in type 2 diabetes mellitus (T2DM) and against diabetic complications by directly interacting with different molecular and cellular pathways that provoke the pathogenesis of T2DM. This article explores the overall beneficial effects of Z. officinale on T2DM and its associated complications. Along with elucidating the beneficial facts of Z. officinale, this article may also aid in understanding the molecular basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 0 publications
0
37
0
1
Order By: Relevance
“…In recent years, effective monomers or extracts from natural plants have been widely applied to the treatment of diabetic nephropathy (DN) [13]. Erzhi formula was composed of Ligustri lucidi fructus and Eclipte herba by the ratio 1:1 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, effective monomers or extracts from natural plants have been widely applied to the treatment of diabetic nephropathy (DN) [13]. Erzhi formula was composed of Ligustri lucidi fructus and Eclipte herba by the ratio 1:1 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Rhizomes of the first, known in English as ginger and locally as ada, and cloves of the second, known in English as garlic and locally as roshun, are used in a large number of dishes of Bangladesh, which includes vegetable, fish and meat dishes. The antidiabetic efficacy of Z. officinale rhizomes have been reviewed [2,3]. The efficacy of A. sativum cloves against diabetes and diabetes-induced complications have also been variously reported [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic hepatitis, cirrhosis and fatty liver are the liver diseases for which treatment is complicated . Plant-based therapeutic strategies for the treatment of different diseases are gaining more attention owing to the presence of risk -free phytochemical constituents (Akash et al, 2011;Akash et al, 2014a,b;Akash et al, 2015;Parveen et al, 2014;Ali et al, 2014;Ibrahim et al, 2013;Akash et al, 2015;Rehman et al, 2012). Several studies have confirmed the hepatoprotective effectiveness of several plant extracts (Sadeque et al, 2010;Hegde et al, 2010;Hussain et al, 2014a,b) to cure liver diseases and unveiled their mechanisms of hepatoprotective activity.…”
Section: Introductionmentioning
confidence: 99%